Matching governance mechanisms with transaction-specific investment types and supplier roles: An empirical study of cross-border outsourcing relationships - Wang, L.; Zhang, C.; Jiang, Fuming (Elsevier, 2019)
Drawing from transaction cost economics (TCE) and relational view (RV), we develop a contingency framework that matches governance mechanisms with different types of supplier transaction specific investments (TSIs) in cross-border outsourcing relationships. We further examine the three-way interaction effects between governance mechanisms, TSI types, and supplier roles in cross-border outsourcing relationships. Using data collected from 324 managers of local suppliers in China and 162 managers working for international buyers located in 15 different OECD countries, we find that while relational governance is more effective at safeguarding supplier human TSIs, it is not an effective solution for safeguarding supplier physical TSIs. In contrast, formal contracts help safeguard supplier physical TSIs against international buyer opportunism, but they are ineffective at safeguarding local supplier human TSIs. Moreover, we find that the interaction effect between formal contracts and supplier physical TSIs is stronger for original equipment manufacturers (OEMs) than for original design manufacturers (ODMs), whereas the interaction effect between relational governance and supplier human TSIs is stronger for ODMs than for OEMs. Theoretical and anagerial implications of the findings follow.